Nilai-Nilai Pendidikan Islam dalam Tradisi Damar pada Masyarakat Kampung Patipi Pulau Kabupaten Fak-Fak - M. Syukri Nawir; Muhamad Yusuf; Suparto Iribaram; Afan Garamatan; Nining Puji Lestari (Jurnal Pendidikan Humaniora, 2022)
Abstract: The study's goal was to explain Islamic education ideals in the Damar tradition in Patipi Pulau Village, Fak-fak Regency. It is a qualitative study with a social phenomenological method, involving observations, interviews, and recording utilizing Miles and Huberman's flow model analysis technique. The study's findings: The festiveness of the mosque on the night of Lailatul Qadar is a practice carried out by the community in Patipi Pulau Village by participating in religious rituals together, with delight, such as breaking the fast, offering alms, torch procession, and reading the Qur'an. Volunteerism, which is honesty and refraction, is the basis for alms to mosque administrators. People's lives are affected by high kinship values. Culture and religion come together to produce a sense of community among residents, a sense of solidarity that is raised spontaneously by the community in the practice of traditions. Devotion, charity, alms, al-ukhuwah, Khuluqiyah, al-Masuuliyyah, al-Munfiqun, and friendship are among the Islamic educational ideals taught in the tradition. Mosque administrators carry out their duties and obligations with seriousness since caring for the mosque is a noble responsibility that is passed down from generation to generation or passed down via inheritance. The community retains meaningful traditions (beliefs, knowledge, and habits) as a means of organizing, accepting, and creating subsequent interactions and acts based on common understanding.Abstrak: Tujuan penelitian adalah untuk menjabarkan nilai-nilai pendidikan Islam dalam tradisi Damar di Kampung Patipi Pulau Kabupaten Fak-fak. Merupakan penelitian kualitatif, dengan pendekatan fenomenologi social, melakukan observasi, wawancara dan dokumentasi, dengan menggunakan tehnik analisis model alir dari Miles dan Huberman. Hasil penelitian: Meriahnya Masjid pada malam Lailatul Qadar merupakan pembiasaan yang dilakukan masyarakat di Kampung Patipi Pulau dengan melakukan aktivitas keagamaan bersama, dengan kegembiraannya melalui berbuka puasa, pemberian sedekah, pawai obor, membaca Qur’an. Sedekah pada pengurus Masjid didasarkan kesukarelaan yang merupakan ketulusan serta pembiasan. Nilai-nilai kekerabatan yang tinggi mempengaruhi kehidupan masyarakat. Budaya dan agama menyatu menciptakan kebersamaan diantara warga, merupakan solidaritas yang dimunculkan masyarakat secara spontan dalam pelaksanaan tradisi. Rangkaian kegiatan dalam tradisi mengandung nilai pendidikan Islam seperti: Ketaqwaan, Amaliyah, Sedekah, al-ukhuwah, Khuluqiyah, al-Masuuliyyah, al-Munfiqun, serta silaturahmi. Pengurus Masjid melakukan tugas dan tanggungjawabnya dengan keikhlasan, disebabkan mengurus Masjid adalah tugas mulia yang dilakukan turun temurun atau pewarisan. Masyarakat mempertahankan tradisi yang memiliki makna (keyakinan, pengetahuan serta kebiasaan), sebagai cara mengatur, menerima, berbagai tradisi yang dianggap baik serta mendasari pemahaman bersama dan mengembangkan interaksi dan tindakan lebih lanjut.